2018
DOI: 10.1016/j.sjbs.2017.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Irisin protects macrophages from oxidized low density lipoprotein-induced apoptosis by inhibiting the endoplasmic reticulum stress pathway

Abstract: Irisin is a newly discovered myokine which can relieve metabolic disorders and resist atherosclerosis. The effects of irisin on ox-LDL-induced macrophage apoptosis and endoplasmic reticulum stress-related pathways were observed . RAW264.7 macrophages were cultured and pretreated with irisin at 20, 40 and 80 ng/ml for 30 min, followed by culture with 100 mg/L ox-LDL and 5 mg/L tunicamycin (TM) for 12 h. The cell viability and apoptosis were detected by MTT assay and annexin V-FITC double staining. The nuclear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
(36 reference statements)
3
16
0
Order By: Relevance
“…Irisin has been previously reported to protect cells from apoptosis [21] and promote cell proliferation [22,23]. We next detected fibrosis and cardiomyocyte proliferation in hearts.…”
Section: Irisin Decreased Cardiomyocyte Apoptosis and Fibrosis In Posmentioning
confidence: 87%
“…Irisin has been previously reported to protect cells from apoptosis [21] and promote cell proliferation [22,23]. We next detected fibrosis and cardiomyocyte proliferation in hearts.…”
Section: Irisin Decreased Cardiomyocyte Apoptosis and Fibrosis In Posmentioning
confidence: 87%
“…HFD promotes metabolism via exogenous pathways that results in elevated levels of low-density lipoprotein (LDL) that can be converted to oxidised LDL (oxLDL). oxLDL interactions with blood vessel walls cause endothelium dysfunction (7,8). Moreover, oxLDL stimulates formation of lipid peroxide free radicals, which, together with other free radicals, can cause a decrease in activity of antioxidant enzymes such as superoxide dismutase (SOD) (1,9).…”
Section: Introductionmentioning
confidence: 99%
“…Innate and adaptive immune system responses can also be activated in response to signaling mediated by oxLDL (10,11). Increased levels of oxLDL promote differentiation of mononuclear cells (monocytes) into macrophages (8). Macrophages and dendritic cells that express Toll-like receptors that bind oxLDL scavenger receptors initiate an inflammatory signaling pathway by secreting pro-inflammatory cytokines such as tumour necrosis factor α (TNF-α) (12).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, high amounts of exogenous lipids can change the biophysical properties of the ER membrane and launch the UPR by activation of PERK and IRE1 in the lipid bilayer [ 28 ]. Furthermore, various stress factors, including oxidized LDL (oxLDL) and oxysterols, can negatively affect the process of protein folding in the ER by perturbations of the ER lipid bilayer composition, which leads to UPR activation [ 29 , 30 ]. It has been also shown that modified atherogenic LDL, such as oxLDL, can cause up-regulation of scavenger receptors such as SR-A, CD36, and lectin-like oxidized LDL receptor-1 (LOX-1) via activation of ER stress response [ 31 , 32 , 33 ].…”
Section: The Role Of Er Stress In the Formation Of Foam Cellsmentioning
confidence: 99%
“…For the first time, it was also shown that oxidized HDL (oxHDL), unlike native HDL, can activate macrophage apoptosis by inducing the ER stress/CHOP pathway through enhanced oxidative stress, which can be mediated by interaction of oxHDL with TLR4 [ 55 ]. In addition, suppression of the ER stress/CHOP pathway in macrophages caused by oxLDL could be achieved by stimulating the expression of apolipoprotein A-I [ 29 ]. Sphingosine-1-phosphate (S1P) is one of the components of HDL, which has an anti-apoptotic effect and promotes alternative (anti-inflammatory) polarization of macrophages, and an important player in various processes in macrophages [ 56 ].…”
Section: The Role Of Er Stress In Apoptosismentioning
confidence: 99%